COMMUNITY BASED TOURISM (CBT) PROGRAM: TOURISM VILLAGE DEVELOPMENT BASED ON LOCAL CULTURE, DIGITAL TECHNOLOGY, CREATIVE ECONOMY IN SIDATAPA VILLAGE, BULELENG REGENCY - Setiawati, Rahmi; Syam, Nia Kurniati (Jurnal Komunikasi dan Bisnis, 2023)
Sidatapa Village is one of the villages in Banjar District, Buleleng Regency which has unique historical and cultural values. The problems that exist in Sidatapa Village to date include: connectivity of tourism locations as tourist areas, homestay management, community capacity as the subject of area management n. This study uses a qualitative method with data collection through interviews, observation and literature study used in the form of literature review; and in the form of policy documents related to Community Based Tourism and Tourism Villages. The results of the research developed are, by empowering the community by forming tourism-aware cadres and providing strengthening of economic capacity in managing local village potential, managing traditional houses used as homestays using an economic solidarity approach, and promoting sustainable tourism. This program uses a solidarity approach, in which all members of the community are involved and share resources.